“Mongering Is a Weird Life Sometimes”: Discourse Analysis of a Sex Buyer Online Community - Alves, Catarina D. B. (Violence against women, 2021)
The purpose of this study was to examine the narrative of sex buyers in an unmoderated online forum. Using a feminist critical discourse analysis (FCDA) and intersectionality approach, we investigated overt and subtle ways power inequalities were present in the discourse of men who bought sex in Chicago. Four main themes emerged: (a) toxic masculinity; (b) violence against women; (c) intersectionality of sexuality, race, and age; and (d) the need to maintain the community. Our findings imply that johns’ self-described monger identity is closely associated with maintaining, perpetrating, and minimizing violence against women.